Sustained Lesion and Shedding Rate Reductions in Genital Herpes Patients 24 Months after Immunization with GEN-003, a Genital Herpes Immunotherapy. (4th October 2017) - Heineman, Thomas; Mcneil, Lisa K; Oliphant, Thomas; Natenshon, Andrew; Van Wagoner, Nicholas; Flechtner, Jessica B; Hetherington, Seth; ,
Abstract: Background: Herpes simplex viruses (HSVs) are the main cause of genital ulcers worldwide. GEN-003 is an investigational genital herpes immunotherapy composed of HSV-2 antigens gD2DTMR and ICP4.2, and the saponin-based adjuvant Matrix-M2 TM (MM2). In a Phase 2 dose-ranging study (GEN-003-002), 3 doses of GEN-003 reduced HSV-2 lesion rate (percent of days with genital lesions) and anogenital HSV-2 shedding rate (percent of days with detectable virus). The antiviral effect of GEN-003 persisted to 12 months after the 3-dose vaccination regimen. We report here the results of an extension study to evaluate efficacy and immunogenicity of GEN-003 at 24 months post-vaccination. Methods: GEN-003-002 subjects who received at least 1 dose of GEN-003 (dose groups: 30 or 60 µg of antigens combined with 25, 50 or 75 µg of MM2) were eligible to enroll in the extension study. At 24 months post-vaccination, anogenital swabs were collected twice daily for 28 days for HSV-2 DNA detection by quantitative PCR. During this period, subjects also reported genital herpes lesion data via a daily reporting tool. Blood samples were collected at the end of the swab collection period to evaluate humoral and cellular immune responses. HSV-2 immunoglobulin G (IgG) was measured by ELISA, and HSV-2 neutralizing antibodies were measured by a colorimetric assay. Cellular responses were evaluated in peripheral blood mononuclear cells using an interferon-g/granzyme B Fluorospot assay. Results: 140 subjects were enrolled. At 24 months, those in the two best-performing GEN-003-002 study groups, 60 µg antigens combined with either 50 or 75 µg MM2 (60/50 and 60/75, respectively), recorded decreased mean viral shedding rates of 58% and 69% below baseline, similar to the 12-month shedding rate reductions, and mean anogenital lesion rates of 77% and 39% below baseline, respectively (Fig 1 ). In all dose groups, mean IgG titers to ICP4.2 and gD2ΔTMR were sustained from 12 to 24 months. Similarly, mean neutralizing antibody titers did not change significantly from month 12 to 24. Conclusion: GEN-003 induces reductions in HSV-2 shedding and genital herpes lesion rates that persist to 24 months following treatment. Humoral immune responses to GEN-003 are maintained at 24 months after immunization. Disclosures: T. Heineman, Genocea Biosciences: Employee, Salary. L. K. Mcneil, Genocea Biosciences: Employee, Salary. T. Oliphant, Genocea Biosciences: Consultant, Consulting fee. A. Natenshon, Genocea Biosciences: Employee, Salary. N. Van Wagoner, Genocea Biosciences: Consultant, Research support and Travel support to present at scientific meetings .J. B. Flechtner, Genocea Biosciences: Employee, Salary S. Hetherington, Genocea Biosciences: Employee, Salary/